Democratic Parenting in Terms of The Self-Concept of Tionghua Students - Salim, Jennifer Creszentia; Hartati, Merry; Yuliana, Yuliana; Tandera, Ruben Luis; Hartini, Sri; Tarigan, Eltalina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Today, many children are not only required to learn formal education but also have to learn non-formal education. One of them is to have a good character. Parenting plays an important role in the formation of children's character. From an early age, children will be introduced to how to behave well, good communication, and so on. The character of the child will have a great influence in the future for the survival of the child. Democratic parenting is a series of parental actions in interacting with adolescents that apply a parenting style that encourages adolescents to be independent but still provides boundaries and control over adolescent actions, provides opportunities for dialogue, is warm and nurturing and shows pleasure and support in response to adolescent constructive behavior. The purpose of this study is to test and prove the relationship between democratic parenting in terms of self-concept. The research sample consisted of 115 students of Sultan Iskandar grade 1 high school. Young through Purposive Sampling Technique. The research data were collected using a democratic parenting scale consisting of 19 items and a self-concept scale consisting of 21 items.